The Effect of Telecommuting on Information Acquisition: Evidence from the U.S. Patent Office - Baek, In Gyun (The Accounting Review, 2023)
ABSTRACT I examine whether telecommuting, a work arrangement in which employees do not travel to a workplace, affects the acquisition of new information in an environment where thorough search and acquisition of information are essential. On the one hand, telecommuting may impede information acquisition due to reduced communication with colleagues. On the other hand, telecommuting may facilitate information acquisition due to relaxed time pressure (via not having to commute) and increased attentional resources (via quieter and uninterrupted working environments). I find employees' acquisition of new information increases following telecommuting. Further, I find that this effect is greater for employees under greater time pressure and employees experiencing greater distractions at the workplace before telecommuting and find that telecommuting causes adverse consequences for employees least responsive to organizations' incentive systems. Finally, I find that work quality improves following telecommuting. My results suggest telecommuting benefits employees performing knowledge-intensive tasks by facilitating employees' information acquisition.